2008
DOI: 10.1111/j.1540-6210.2008.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Morally Committed Citizens? A Study of the Antecedents of Public Service Motivation

Abstract: This study examines the relationship between public service motivation and antecedents believed to be important determinants of moral commitment. Research conducted during the past decade indicates that public service motivation is a valid construct that is useful for predicting outcomes that are important to public organizations and to society. The sample for the empirical study consists of winners of the Daily Point of Light Award and the President’s Community Volunteer Award. Antecedents studied are volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(205 citation statements)
references
References 39 publications
9
190
2
4
Order By: Relevance
“…In recent years, using the scale and dimensions of Perry's PSM (1996), many researchers have tested the antecedent and effect factors of PSM (Perry, 1997(Perry, , 2000Choi, 2004;Camilleri, 2006;Castaing, 2006;Camilleri, 2007;Moynihan and Pandey, 2007;Perry et al, 2008;Christensen and Wright, 2011;Vandenabeele, 2011;Kachornkittiya et al, 2012). From the test results, some studies claimed that PSM was viable for any condition and environment (Crewson, 1995;Vandenabeele et al, 2004;Bertelli, 2006;Leisink and Steijn, 2009;Vandenabeele, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, using the scale and dimensions of Perry's PSM (1996), many researchers have tested the antecedent and effect factors of PSM (Perry, 1997(Perry, , 2000Choi, 2004;Camilleri, 2006;Castaing, 2006;Camilleri, 2007;Moynihan and Pandey, 2007;Perry et al, 2008;Christensen and Wright, 2011;Vandenabeele, 2011;Kachornkittiya et al, 2012). From the test results, some studies claimed that PSM was viable for any condition and environment (Crewson, 1995;Vandenabeele et al, 2004;Bertelli, 2006;Leisink and Steijn, 2009;Vandenabeele, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For people who do ordinary amounts of volunteering and charitable giving, religion is just one motivation among others, but for highly prosocial people, religion seems to be very important. Perry et al (2008) and Colby and Damon (1992) came to similar conclusions, but they used selective samples of highly prosocial people only. This study replicates their findings in a nationally representative random sample that includes less prosocial respondents as a comparison group.…”
Section: Discussionmentioning
confidence: 65%
“…Two studies of highly prosocial "moral exemplars" (Colby and Damon 1992;Perry et al 2008) found that the majority cited religion or spirituality as a reason for helping others. Furthermore, these exemplars did not compartmentalize their lives into religion, personal life, and helping work, but considered their spiritual or religious beliefs, helping behaviors, and personal identity to be "highly integrated" into a single whole (Perry et al 2008: 452).…”
mentioning
confidence: 99%
“…Johns and Saks [26] discuss that during recessions, a typical scenario is that employees have to stay in an organization they hate, which is related to low affective and high continuance commitment. Job security is an especially important antecedent of continuance commitment for employees in the public sector [39,42]. Continuance commitment is also often associated with antecedents like investments and alternatives.…”
Section: Organizational Commitmentmentioning
confidence: 99%